INI‐1 (SMARCB1)–Deficient Undifferentiated Sinonasal Carcinoma: Novel Paradigm of Molecular Testing in the Diagnosis and Management of Sinonasal Malignancies. (12th June 2020) - Shaverdashvili, Khvaramze; Azimi‐Nekoo, Elham; Cohen, Perry; Akbar, Nadeem; Ow, Thomas J.; Halmos, Balazs; Castellucci, Enrico
Abstract: Sinonasal tumors consist of a group of rare heterogeneous malignancies, accounting for 3%–5% of all head and neck cancers. Although squamous cell carcinomas make up a significant portion of cancers arising in the sinonasal tract, there are a variety of aggressive tumor types that can present with a poorly differentiated morphology and continue to pose diagnostic challenges. Accurate classification of these unique malignancies has treatment implications for patients. Recent discoveries have allowed more detailed molecular characterization of subsets of these tumor types, and may lead to individualized treatments. INI‐1 (SMARCB1)–deficient sinonasal carcinoma is a recently identified subtype of sinonasal malignancy, which is characterized by deletion of the INI‐1 tumor suppressor gene. Loss of INI‐1 expression has emerged as an important diagnostic feature in several human malignancies including a subset of sinonasal carcinomas. In this article, we present a case of INI‐1 (SMARCB1)–deficient sinonasal carcinoma, provide an overview of recent advances in histological and molecular classification of sinonasal malignancies, and discuss challenges of caring for patients with these rare malignancies, as well as potential treatment implications. Key Points: Clinicians and pathologists should recognize that a variety of sinonasal tumors can present with a poorly differentiated morphology that warrants further workup and molecular classification. Routine workup of poorly or undifferentiated sinonasal tumors should include testing for INI‐1/SMARCB1, SMARCA4, and NUT. Patients with these molecularly defined subsets of tumors may benefit from clinical trials that seek to exploit these molecular alterations. The EZH2 inhibitor, tazemetostat, has demonstrated some antitumor activity in INI‐1–deficient tumors, and is currently under investigation. Abstract : Sinonasal tumors are a group of uncommon heterogeneous malignancies that account for 3% to 5% of all head and neck cancers. This article presents a case of INI‐1‐ (SMARCB1)‐deficient sinonasal carcinoma and discusses the challenges of caring for patients with these rare malignancies.